2020
DOI: 10.1111/jre.12773
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory and macrophage polarization effects of Cranberry Proanthocyanidins (PACs) for periodontal and peri‐implant disease therapy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
(95 reference statements)
2
26
0
Order By: Relevance
“…Conferring to the mentioned immunological processes, several studies have shown that M1 polarization is in fact associated with osteolytic processes [17,28,30]. Moreover, some studies have also implied that macrophage switch from M1 to M2 phenotype plays a central role to decrease chronic inflammation and osteolytic effects [9,28,30].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Conferring to the mentioned immunological processes, several studies have shown that M1 polarization is in fact associated with osteolytic processes [17,28,30]. Moreover, some studies have also implied that macrophage switch from M1 to M2 phenotype plays a central role to decrease chronic inflammation and osteolytic effects [9,28,30].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that pro-inflammatory reactions at host tissues can be induced by bacteria sub-products (i.e., lipopolysaccharides) or interferon (IFN)-g which subsequently activate M1 phenotype promoting inflammation [10,28]. In chronic inflammatory diseases, CD4-T-cell-centered processes stimulate T-helper cells to promote or counteract inflammation and osteolysis, playing a pivotal role on macrophage polarization [1,9,29]. In this scenario, Th1 and Th17 cells are associated to disease progression, upregulating inflammation, and osteolytic effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Galarra ga-Vinueza et al 2020) [12] Unverified commercial proanthocyanidin (PA) purchased at ChemFace, with molecular weight =594.52 and untypical structure.…”
Section: Influence On Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%